The influence of ESG, profitability, and leverage on firm value with tax avoidance as an intervening - Yulinda, Fany (WIM Solusi Prima, 2025)
This research aims to determine the influence of Environmental, Social Governance (ESG), profitability, and leverage on company value with tax avoidance as an intervening variable. The research method used is descriptive and verification. The sampling technique used is non-probability sampling with purposive sampling technique, so the samples used in this research are 80 annual reports of general manufacturing companies listed on the indonesia stock exchange (IDX) during 2018-2022. The data analysis technique used in this research is path analysis using Eviews 12. The research results show that Environmental, Social, Governance (ESG), profitability and leverage influence tax avoidance. Apart from that, the research results show that Environmental, Social, Governance (ESG), profitability, leverage and tax avoidance influence firm value. Meanwhile, based on indirect test results, it shows that there is an indirect influence of Environmental, Social Governance (ESG), profitability and leverage on firm value through tax avoidance.